Corporate Change After the Global Financial Crisis - Ivo Arnold (Credit and Capital Markets – Kredit und Kapital, 2020)
This paper examines the strategic response of the Dutch bank ING to the global financial crisis. Prior to the crisis, ING was a prominent global exponent of direct banking, using the so-called pure play internet (PPI) business model. PPI banking is a hybrid business model that combines features of relationship and transaction banking. Downsides of this business model are that it may lead to overexposure in securities and that it may attract savers that have an above-average sensitivity to interest rates or risk. Using data on the geographical activities of ING, the timeline of relevant events in the history of ING and strategy statements of ING management, we examine how ING has responded to the strategic challenges of the crisis. We conclude that PPI banking should be viewed more as a market penetration strategy than as a full-blown business model that is tenable in the long run.
Keywords: G01; G21; 330; Financial Stability; Direct Banking; Business Models